Kualitas Jasa terhadap Kepuasan Pasien Rumah Sakit Swasta di Kota Bandung - Bulan Tati Fitria; Irena Larashati; Robbi Saepul Rahman (Kontigensi : Jurnal Ilmiah Manajemen, 2018)
Hospital gives health services to the publict to fulfill the patients’ needs and wants. They provides excellent image in production and high quality service. The public’s awareness is increased on the importance of health. Therefore, the best health service is urgently needed. Thus, there must be a further study about the quality of public hospital in Bandung. This study uses the descriptive verificative method. Moreover, this study uses path analysis to analyze the data. There are 317 respondents from four public hospitals as the samples with accidental sampling technique. The result shows the impact of direct evidence, empathy, reliability, responsiveness, the certainty on patients of private hospital are 83.5%. While the other factors that were not analyzed and have an impact on patients’ satisfaction is shown by epsilon 0.165 or 16.5%. Hopefully, the result of this study is beneficial for the growth of management science, especially the marketing management of private hospital in Bandung.